1981
DOI: 10.1172/jci110327
|View full text |Cite
|
Sign up to set email alerts
|

Follicle-stimulating Hormone and Human Spermatogenesis

Abstract: A B S T R A C T The role of follicle-stimulating hormone (FSH) in the control of spermatogenesis is not well established in any species, including man. We studied the effect of an experimentally-induced, selective FSH deficiency on sperm production in normal men. After a 3-mo control period, five normal men received testosterone enanthate (T) 200 mg i. m. weekly to suppress luteinizing hormone (LH) and FSH, until three successive sperm counts revealed azoospermia or severe oligospermia (sperm counts <3 million… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

1983
1983
2000
2000

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(39 citation statements)
references
References 30 publications
5
34
0
Order By: Relevance
“…Furthermore, no agent presently available for experimental use can produce a selective deficiency of LH or FSH in man. We have previously reported that human chorionic gonadotropin (hCG) can reinitiate sperm production in gonadotropin-suppressed normal men, despite undetectable blood FSH levels and urinary excretion of FSH less than that of prepubertal children (16). Our results demonstrated that normal serum levels of FSH are not an absolute requirement for sperm production in man.…”
Section: Introductionmentioning
confidence: 53%
“…Furthermore, no agent presently available for experimental use can produce a selective deficiency of LH or FSH in man. We have previously reported that human chorionic gonadotropin (hCG) can reinitiate sperm production in gonadotropin-suppressed normal men, despite undetectable blood FSH levels and urinary excretion of FSH less than that of prepubertal children (16). Our results demonstrated that normal serum levels of FSH are not an absolute requirement for sperm production in man.…”
Section: Introductionmentioning
confidence: 53%
“…The replacement regimen achieved physiological levels ofserum LH bioactivity. The hCG replacement regimen used in the third study has been shown previously to achieve a sixfold elevation in serum LH bioactivity (21). Serum inhibin levels increased somewhat more during hCG treatment than during the hLH regimen but were still lower than control levels.…”
Section: Discussionmentioning
confidence: 77%
“…Serum pressed to levels comparable to those of prepubertal or hypogonadotropic subjects (21). After hFSH treatment, FSH levels then increased to just above the upper limit of the normal range (273±44 ,ug/liter).…”
Section: Experimental Protocolmentioning
confidence: 89%
See 1 more Smart Citation
“…Sperm count recovery was defined as the first of three normal sperm counts (Ͼ20 ϫ 10 6 /mL) with at least one value equal to the subject's mean baseline count. Sperm counts were determined by a Coulter counter (Coulter Electronics, Inc., Hialeah, FL), and concentrations of Ͻ15 ϫ 10 6 /mL were confirmed by direct determination with use of a hemocytometer (14,15). Sperm motility assessment was performed according to the WHO laboratory manual for the examination of human semen and sperm-cervical mucus interaction (16).…”
Section: Sperm Countsmentioning
confidence: 99%